Feasibility Study of Podo Town Square Gemek Pedestrian, Kedungwuni District, Pekalongan Regency - Aris Krisdiyanto; Kemmala Dewi; Archi Rafferti Kriswandanu; Althea Serafim Kriswandaru; M. Makhfud Riyadi (International Journal of Social Service and Research, 2022)
The Institute of Technology and Science (ITS) campus, Pusmanu Polytechnic, SMA Negeri 1 Kedungwuni, SMK Negeri 1 Kedungwuni, SMP Negeri 2 Kedungwuni as an educational center, There are shophouses along the right and left side of the road as a trading place. This is the reason why so many people come to the area. So in the Podo-Surabaya segment, human movement in the area is high. The more visitors who come to the place will impact the concentration of pedestrians. With a large pedestrian flow and the presence of street vendors and illegal parking at several points along the sidewalk, it will significantly affect the comfort and flexibility of pedestrians. For this reason, it is necessary to plan for improving pedestrian facilities in the area. To obtain the minimum width, the required sidewalk width, and pedestrian facilities are calculated according to the Technical Guidelines no. 032/T/BM/1999 “Guidelines for Planning Pedestrian Paths on Public Roads, Minister of Public Works Decree No. 468/KPTS/1998 "Technical Requirements for Accessibility in Public Buildings and the Environment," Director General of Highways No.007/T/BNKT/1990 "Guidelines for Using Sidewalks," Minister of Public Works Regulation No. 03/PRT/M/2014 "Guidelines for Planning, Provision, and Utilization of Pedestrian Network Infrastructure and Facilities in Urban Areas," Technical Guidelines no. 022/T/BM/1999 "Accessibility Requirements on Public Roads." The results of the design are carried out with the AutoCAD program. From the calculation of pedestrian walking speed, the average rate is 43.80 m/minute, from the analysis of the minimum width obtained 1,6 meters.